Escravas, prostitutas e médicos: normalizando modos de vida da Corte do Rio de Janeiro - Castro, Marcelo Ribeiro de (2011)
The study that I present it argues the tactics of survival adopted by the slaves and the prostitutes who had inhabited in the urban spaces of the Court of Rio de Janeiro, in the understood period enters 1845 the 1890. Some of these tactics are underlying in the theses of the College of Medicine of Rio de Janeiro, defended in century XIX. As objective generality, the study it proposes to evaluate main social determinatives of century XIX that they justify the tactics of resistance adopted by the slaves and the resident prostitutes in the urban spaces of the Court of Rio de Janeiro. Moreover, it is investigated from the studies of Foucault (1972), the genealogy of the present power in the medical speeches - theses and projects -, that they deal with the ways of being and constituting slaves and prostitutes in the urban spaces of the Court of Rio de Janeiro, enters the years of 1845 the 1890. The investigated questions are: 1) How the tactics of resistance adopted by the slaves and the prostitutes opened breaches for new forms of life of these women? 2) The medical prescriptions of hygienical norms for slaves and prostitutes occurred in result of the imperial elite to need more salubrious a public and private service, or because some doctors were vain of the necessity of if extending doctor-hygienical cares e, later, sanitary to all the inhabitants of the urban areas of the Court, independently of the sex and the social condition? The interstice between years 1845-1890 was chosen by identifying here the sprouting of the first curricular reforms of the Colleges of Medicine of Brazil - FMRJ and FMBA, first doctors formed in ground Brazilian, beyond the ascension and of the decline of the social organization, economic politics and of the Imperial State. The studies of Possenti (2008) and, mainly, of Certeau (2008) evidence tactics and ways of survival adopted by the slaves and prostitutes capable to confer to these women the condition of historical citizens. The results of this thesis indicate that the subjectivities present in the works, practical of leisure, the sexual relation, the types of clothes, the places of housing, feeding and in the forms of contraction of unions have been primordial so that these women occupied spaces and developed tasks until then understood as exclusive for the masculine sex. This way, such tactics had contributed of some form so that some slaves and prostitutes became responsible direct for its proper sustenance, as well as the one of its familiar ones